Pengaruh Investasi dan Pertumbuhan Domestik Regional Bruto(PDRBHK) terhadap Jumlah Angkatan Kerja di Provinsi Sumatera Utara: Penelitian - Monika Caramoy Sitorus; Jemely Prisya Simanjuntak; Yendita Pakpahan; Renaldi Enriko Sigalingging (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine how investment and Gross Regional Domestic Product at Constant Prices (GRDPHK) affect the number of workers needed in North Sumatra Province between 2009 and 2024. The study used a quantitative method with a multiple linear regression (OLS) model and data from the Central Bureau of Statistics and Bank Indonesia. The results show that investment does increase the number of workers, and its effect is quite clear, while GRDPHK also has a positive effect, although not very strong. When viewed together, these two factors simultaneously influence the number of workers with an explanation level of 78.97%. Investment is the main factor in increasing employment, while GRDPHK growth needs to be placed in sectors that require a lot of labor to have a real impact on job creation.